2012
DOI: 10.4236/gm.2012.24011
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Acid Leaching of Low Grade Manganese Ores

Abstract: Manganese recoveries from low-grade ores using organic acids as reducing agents were investigated in the present work. The acid leaching potential of both oxalic acid and citric acid were estimated. Manganese leaching amount were measured by using standard manganese curve and estimated by titration method. Effects of various acid concentrations on leaching efficiency were studied. The observed result suggested prominent manganese recovery of 66% by oxalic acid at 2 M concentration whereas citric acid had less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The numerous microbe-mineral interactions act as a link to understand the innate mechanisms of certain phenomena taking place in nature and assist to study the mineral surfaces and changes occurring in minerals with respect to time and action of microbial species (Mapelli et al 2012). Over the past few years, the interactions of selected microorganisms for beneficiation and bioleaching of the low-grade minerals/mineral wastes have been reported (Baba et al 2011;Erust et al 2013;Esther et al 2013;Panda et al 2012aPanda et al , b, 2013aPanda et al , 2015 and gradually gaining lot of importance for providing eco-friendly methods of environmental reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…The numerous microbe-mineral interactions act as a link to understand the innate mechanisms of certain phenomena taking place in nature and assist to study the mineral surfaces and changes occurring in minerals with respect to time and action of microbial species (Mapelli et al 2012). Over the past few years, the interactions of selected microorganisms for beneficiation and bioleaching of the low-grade minerals/mineral wastes have been reported (Baba et al 2011;Erust et al 2013;Esther et al 2013;Panda et al 2012aPanda et al , b, 2013aPanda et al , 2015 and gradually gaining lot of importance for providing eco-friendly methods of environmental reclamation.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, using laterite ores from Western Australia and Indonesia, McKenzie et al [346] reported that citric, tartaric and pyruvic acids increased the yield of soluble nickel for limonite type ores. In a comparative study, Das et al [347] showed that oxalic acid was more efficient at extracting manganese (66%) than citric acid (40%) from low-grade ferromanganese ore, attributing the difference to the reducing capacity of oxalic acid and its affinity for manganese complexation.…”
Section: Leaching With Acidophilic Heterotrophs/organic Acidmentioning
confidence: 99%
“…In this case, cell adhesion to the mineral surface is an absolute essential prerequisite. The indirect mechanism is mainly based on the production of metabolites like organic acid which in turn causes metal solubilization Das, Swain, Panda, Pradhan, & Sukla, 2012;Ghosh, Mohanty, Akcil, Sukla, & Das, 2016).…”
Section: Introductionmentioning
confidence: 99%